Determinan Nilai Perusahaan Sebuah Literasi Pada Jakarta Islamic Index - Dini Tsaa Afnitasari; Pancawati Hardiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The development of investment in Indonesia in 2022 has increased, one of which is investing in sharia stocks, because at the beginning of 2023 sharia stocks showed an increase of 5.35%. Sharia stocks on the Jakarta Islamic Index (JII) consist of 30 companies. This study aims to find empirical evidence about the effect of tax planning and leverage on firm value with firm size as a moderating variable. The data in this study uses secondary data for the company's financial reports at JII for 2017-2021. The sampling technique with the purposive sampling method approach obtained a number of 144 companies for five years of observation. The results of the study found that tax planning had a significant negative effect on firm value, while leverage had a significant positive effect on firm value. Firm size is able to strengthen the relationship between tax planning and firm value, but company size is unable to moderate the relationship between leverage and firm value. Keywords: Tax Planning, Leverage, Firm Value, Firm Size